The Best of Technology Writing 2008 - Clive Thompson (University of Michigan Press, 2008)
The Best of Technology Writing 2008 proves that technology writing is a bona fide literary genre with some of the most stylish, compelling, and just plain readable work in journalism today. The third volume in this annual series, The Best of Technology Writing 2008 covers a fascinating mix of topics—from a molecular gastronomist's recipe for the perfect gin and tonic; to "the Mechanism," an ancient Greek artifact that might be the world's first laptop computer; to social media, privacy, and what is possibly the biggest generation gap since rock 'n' roll.